Caries prevalence of the first permanent molar and associated factors among second-grade students in Xiangyun of Yunnan, China: A cross-sectional study - Mingshan Liu; Xiaoqin Xu; Qianqian Song; Hongmei Zhang; Fang Zhang; Guangyun Lai (Frontiers Media S.A., 2022)
PurposeThis study aimed to explore the caries prevalence of the first permanent molar (FPM) and the associated factors among second-grade students in Xiangyun of Yunnan, China.Materials and methodsA cross-sectional survey was conducted in Xiangcheng Town, Xiangyun County, China, from September to November 2020. The methodology recommended by WHO was used for the dental examination. All the parents were required to complete a questionnaire to collect information on children's family background, dietary habits, oral health behaviors and parental oral health-related knowledge. The tests of significance used were the chi-square test. The association between dental caries prevalence and its associated factors was investigated using logistic regression analysis. Statistical significance was set at P < 0.05.ResultsData of 1,295 second graders consisting of 665 males and 630 females were analyzed. The caries prevalence of FPM was 47.6%, and the mean DMFT was 1.11 ± 1.394 in this sample. Among all the children with caries, the filling rate is meager, 2.6%. There were statistically significant differences in the caries prevalence of FPM among age groups. No significant difference existed between the sexes. Logistic regression analysis showed that the most significantly associated factors were: consuming desserts at least once a day, no fluoride varnish application experience, worse parental perception of children's oral health status, and incorrect parental knowledge of whether decayed primary teeth need treatment.ConclusionCaries prevalence of FPM among second-grade schoolchildren in Xiangyun was considerably higher than the average prevalence nationwide in China. As China aims to reduce dental caries to <25% of 12-year-old children in 2030, the local government of remote regions like Xiangyun needs to do much more to achieve this goal. Results of this study could provide a framework for ongoing and future public oral health programs and policy planning in Xiangyun, with particular attention to early preventive and therapeutic measures.